New prebiotic chemistry inspired filter media for stormwater/greywater disinfection - Jung, J. (Elsevier, 2020)
Greywater and stormwater have received significant attention due to increasing water scarcity. Passive filtration such as biofiltration has been a popular treatment method with its low energy input and environmental friendliness. However, pathogen removal capacity needs improvement to achieve safe water quality. In this study, a prebiotic chemistry inspired copolymer based on aminomalononitrile and 3,4,5-trihydroxybenzaldehyde (AMNT30) was introduced to develop antimicrobial media for passive filtration. The AMNT30 polymer provided an adhesive coating on zeolite substrates following a spontaneous polymerisation process at room temperature. AMNT30 coated media were investigated for metal loading capacity, surface morphology, E. coli removal and metal leaching after filtration of different water sources (i.e. stormwater, greywater, and deionised water) at low/high conductivity. The coating enhanced metal ion loading on the surface and demonstrated that >8 log reduction of E. coli can be achieved for silver loaded materials compared to a 1 log reduction for copper loaded materials. The coating also increased the stability of the metals on the media irrespective of inflow characteristics. This study provided the first example using AMNT30 to create antimicrobial water purification media. It is expected that this technology will find applications in the water treatment industry